Ring-Closing Metathesis as Methodology for the Synthesis of 2- and 3-Arylbenzo[b]furans - Visser, Melanie; Twigge, Linette; Marais, Charlene; Bezuidenhoudt, Barend C. B. (Synthesis, 2024)
Olefin metathesis, which is well established in the petrochemical industry, is also emerging as a green technology in the manufacture of pharmaceutical and specialty chemicals. Arylbenzofurans are of interest for potential medicinal applications. In this paper we report on the synthesis of various 2-aryl- and 3-arylbenzo[b]furans with natural substitution patterns from readily available starting materials in a strategy that applies ring-closing metathesis with the Grubbs second generation catalyst as key step.
Keywords: arylbenzofurans; metathesis; Grubbs catalyst; allylation; Tebbe methylenation; Grignard reagent; Al(OTf)3